Evaluating cells metabolic activity of bioinks for bioprinting: the role of cell-laden hydrogels and 3D printing on cell survival - Mazzoldi, Elena Laura; Gaudenzi, Giulia; Ginestra, Paola Serena; Ceretti, Elisabetta; Giliani, Silvia Clara (Frontiers in Bioengineering and Biotechnology, 2024)
Tissue engineering has advanced significantly in recent years, owing primarily to additive manufacturing technology and the combination of biomaterials and cells known as 3D cell printing or Bioprinting. Nonetheless, various obstacles remain developing adequate 3D printed structures for biomedical applications, including bioinks optimization to meet biocompatibility and printability standards. Hydrogels are among the most intriguing bioinks because they mimic the natural extracellular matrix found in connective tissues and can create a highly hydrated environment that promotes cell attachment and proliferation; however, their mechanical properties are weak and difficult to control, making it difficult to print a proper 3D structure. In this research, hydrogels based on Alginate and Gelatin are tested to evaluate the metabolic activity, going beyond the qualitative evaluation of cell viability. The easy-to-make hydrogel has been chosen due to the osmotic requirements of the cells for their metabolism, and the possibility to combine temperature and chemical crosslinking. Different compositions (%w/v) are tested (8% gel-7% alg, 4% gel-4% alg, 4% gel-2% alg), in order to obtain a 3D structure up to 10.3 ± 1.4 mm. The goal of this paper is to validate the obtained cell-laden 3D structures in terms of cell metabolic activity up to 7 days, further highlighting the difference between printed and not printed cell-laden hydrogels. To this end, MS5 cells viability is determined by implementing the live/dead staining with the analysis of the cellular metabolic activity through ATP assay, enhancing the evaluation of the actual cells activity over cells number. The results of the two tests are not always comparable, indicating that they are not interchangeable but provide complementary pieces of information.